2013
DOI: 10.1159/000351572
|View full text |Cite
|
Sign up to set email alerts
|

Increased Total Renin Levels but Not Angiotensin-Converting Enzyme Activity in Obese Patients with Polycystic Ovary Syndrome

Abstract: Objective: To investigate the renin-angiotensin-aldosterone system and angiotensin-converting enzyme (ACE) activity in patients with polycystic ovarian syndrome (PCOS). Subjects and Methods: In this case-control study, 41 obese (PCOS) women and 29 healthy controls, matched for age and body mass index, were enrolled. Anthropometric, metabolic, and hormonal patterns, including plasma aldosterone, plasma renin, and ACE activity, were measured in each subject. Results: Plasma renin levels were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The association between PCOS and CV risk factors has been identified in the literature [ 19 , 20 , 21 ]. Svendsen et al [ 22 ] demonstrated that PCOS patients have higher 2nd hour glucose levels during an OGTT test than their non-PCOS peers.…”
Section: Discussionmentioning
confidence: 99%
“…The association between PCOS and CV risk factors has been identified in the literature [ 19 , 20 , 21 ]. Svendsen et al [ 22 ] demonstrated that PCOS patients have higher 2nd hour glucose levels during an OGTT test than their non-PCOS peers.…”
Section: Discussionmentioning
confidence: 99%
“…Alphan et al. (2013) reported that there are increased total renin levels in obese females with PCOS. Treatment of patients with PCOS with angiotensin II receptor blockers was associated with significant decrease in the androgen levels and significant improvement of the menstrual pattern (Jensterle et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PCOS is associated with obesity, metabolic syndrome, hyperinsulinemia, type 2 diabetes, dyslipidemia, and cardiovascular syndrome [5, 6]. Thus, PCOS is an endocrine disorder that presents long-term health risks [7, 8]. …”
Section: Introductionmentioning
confidence: 99%